Кластери у воді - Малафаєв, М. Т.; Воронцова, Ж. В. (НТУ "ХПІ", 2011)
Спираючись на структуру льоду запропонована модель кластерів і взаємодії молекул у них. Визначено необхідні умови існування кластерів.

A model of the structure of clusters of water molecules and the interactions in them based on the properties of the ice structure was proposed. The necessary conditions of existence of clusters of water were determined.
Keywords: взаємодія міжмолекулярна; зв'язок водневий; модель води; льод; intermolecular interaction; hydrogen bonding; H-connection; cluster model of water